Development & evaluation of an animated video on healthy weight gain and energy intake during pregnancy for stunting prevention - Md Sharizam, Muhammad Abdul Hayei Karbaschi; Norman, Muhammad Farhan Hanif; Rostam, Muhamad Ashraf; Ab Hamid, Mohd Ramadan; Abu Seman, Muhamad Sadry; Romli, Rahiwan Nazar; Mohd Shukri, Nor Azwani (International Islamic University Malaysia, 2024)
Introduction: Maternal nutrition during pregnancy is crucial for foetal growth, infant health, and survival. Undernutrition in expectant mothers can cause foetal intrauterine growth retardation, low birth weight, and child stunting. As such, effective communication of nutritional information is essential for promoting healthy behaviours among pregnant women. However, despite the worrying prevalence of stunting in Malaysia and the important role of maternal nutrition during the first thousand days of life, there are limited education tools available regarding the recommended maternal nutrition for stunting prevention. Therefore, this study aimed to develop and evaluate an animated video on healthy weight gain and the recommended total calorie intake during pregnancy to prevent stunting. Methodology: A design-and-development research method was employed to create the video, incorporating expert reviews and systematic evaluation processes. The video content was derived from established guidelines and refined through expert workshops. The Suitability Assessment of Materials (SAM) tool and the Patient Education Materials Assessment Tool for Audiovisual Materials (PEMAT-A/V) were used to evaluate the video’s suitability, understandability, and actionability. This was conducted among a panel of six experts and a subsample of target viewers, comprising 30 women who were pregnant or had been pregnant within the previous 12 months. Results: The video received a 72%